Light‐Directed Soft Mass Migration for Micro/Nanophotonics. Issue 16 (29th April 2019) - Kim, Kwangjin; Park, Haedong; Park, Kyung Jin; Park, Sung Hun; Kim, Hyeon Ho; Lee, Seungwoo
Abstract: In this review, it is argued that soft mass migrations, driven and guided by spatially controlled photopolymerization and photochromic isomerization (also called directional plastic deformation or photofluidization of azobenzene materials), offer toolsets for optical engineers to develop various micro/nanophotonic materials and devices that are not readily available with conventional lithographic methods and self‐assembly techniques. In this direction, the two seemingly different concepts of (i) photopolymerization and (ii) photochromic‐isomerization‐driven mass migrations are tied together, and then recent technological advances in these two fields are summarized, including diffractive optical elements (DOEs), electro‐optic DOE devices, colorimetric sensors, biologically inspired optics, plasmonic devices and near‐field studies, and exceptional point optics. This review establishes the technological viability of light‐directed soft mass migration for the overall evolving field of micro/nanophotonics and its research perspectives. Abstract : Soft mass migration, guided and driven by photopolymerization and photochromic‐isomerization, can enrich the available micro/nanophotonic architectures to significantly expand the range of light–matter interaction. This review combines the seemingly different concepts of photopolymerization and photochromic‐isomerization. Then, their recent progress is contrasted and compared to evaluate their technological viability, and the prospects are envisioned.